2021
DOI: 10.1002/mgg3.1593
|View full text |Cite
|
Sign up to set email alerts
|

Vanishing white matter: Eukaryotic initiation factor 2B model and the impact of missense mutations

Abstract: Background Vanishing white matter (VWM) is a leukodystrophy, caused by recessive mutations in eukaryotic initiation factor 2B (eIF2B)‐subunit genes (EIF2B1–EIF2B5); 80% are missense mutations. Clinical severity is highly variable, with a strong, unexplained genotype–phenotype correlation. Materials and Methods With information from a recent natural history study, we severity‐graded 97 missense mutations. Using in silico modeling, we created a new human eIF2B model structure, onto which we mapped the missense m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 44 publications
0
20
0
Order By: Relevance
“… 5 , 12 There is clear genotype-phenotype correlation, with mild and severe variants. 4 , 11 , 15 , 16 If a mild and a severe variant are compound heterozygous, disease severity is intermediate. 15 Although patients with the same variants tend to have a similar disease course, variation may be considerable, especially in onset ≥4 years, even within families.…”
Section: Introductionmentioning
confidence: 99%
“… 5 , 12 There is clear genotype-phenotype correlation, with mild and severe variants. 4 , 11 , 15 , 16 If a mild and a severe variant are compound heterozygous, disease severity is intermediate. 15 Although patients with the same variants tend to have a similar disease course, variation may be considerable, especially in onset ≥4 years, even within families.…”
Section: Introductionmentioning
confidence: 99%
“…Some missense mutations were predicted to show variable structural effects on the protein, including eIF2Bβ[Thr91Bla], eIF2Bβ[Ser171Phe], eIF2Bβ[Gly200Val], eIF2Bγ [Arg91His], eIF2Bδ [Arg264Trp], eIF2Bδ[Arg357Trp], eIF2Bδ[Arg483Trp], eIF2Bε [Thr79Ile], eIF2Bε[Glu81Leu], eIF2Bε[Arg136His], eIF2Bε[Arg195His], eIF2Bε[His269Pro], eIF2Bε[Arg316Gln], eIF2Bε[Thr91Ala], eIF2Bε[Glu213Gly], eIF2Bε[Arg133His], eIF2Bε[Gly386Val], [Ala403Val] and [Thr432Ile]( Slynko et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have reported a certain correlation between the degree of influence of missense mutations on protein structure and phenotypes, but the results are not consistent. Results from protein prediction software or model analysis of the mutation site function prediction revealed that some mutations with multiple or substantial effects on the eIF2B structure were associated with severe phenotypes, such as eIF2Bε[Thr79Ile], eIF2Bε[Glu81Leu], eIF2Bε[Arg136His], eIF2Bε[Arg195His], eIF2Bε[His269Pro], eIF2Bε[Arg269Gln], eIF2Bε[Arg316Gln]; eIF2Bδ[Arg264Trp], eIF2Bδ[Arg357Trp], eIF2Bδ[Arg483Trp], and eIF2Bγ[Arg91His] ( Slynko et al, 2021 ). Mutations such as eIF2Bβ[Thr91Bla], eIF2Bε[Thr91Ala], eIF2Bε[Ala87Val] and eIF2Bε[Glu213Gly], with predicted minimal influence on the eIF2B structure, were associated with mild disease severity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Age at onset is the only strong predictor of clinical course and outcome (6,10). Sequence variant information does not add predictive information (11). Patients were therefore stratified into six groups according to age at onset of VWM, as follows: younger than 1 year (group 1), 1 year to younger than 2 years (group 2), 2 years to younger than 4 years (group 3), 4 years to younger than 8 years (group 4), 8 years to younger than 18 years (group 5), and 18 years or older (group 6), as previously described (6).…”
Section: Patients With Vwm and Mri Examinationsmentioning
confidence: 99%